Evaluasi Sistem Pengendapan Uranium Pada Batuan Sedimen Formasi Sibolga, Tapanuli Tengah - Sukadana, I Gde; Syaeful, Heri (BRIN Publishing, 2016)
Uranium in nature formed in various deposit type, depends on its sources, process, and depositional environments. Uranium occurrence in Sibolga, hosted in sedimentary rocks of Sibolga Formation, is properly potential to develop; nevertheless, the depositional pattern and uranium mineralization process so far had not been recognized. The research aim is to determine the rock distribution patterns and the existence of uranium grade anomalies based on surface geology and borehole log data. Mineralization occurrences from borehole log data distributed from basalt conglomerate unit (Kgl 1), sandstone 1 unit (Bp 1), conglomerate 2 unit (Kgl 2), and sandstone 2 unit (Bp 2) with their distribution and thickness are thinning to the top. Mineralization distribution in the eastern area, mainly on Kgl 1 unit, dominated by detritus materials from epi-genetic depositional in the form of monazite which is formed along with the formation of granite as its source rock. Meanwhile, mineralization on the upper rocks units formed a channel pattern trending northeast-southwest, which formed in syn-genetic process consist of uraninite, carnotite, and coffinite. Sibolga Formation deposition originated from east to west and uranium deposit formed because of the differences of depositional environment from oxidation in the east to the more reductive in the southwest. The increasing of organic materials in southwest basin caused the reduction condition of depositional environment.